Inflammation in Metabolic Cardiomyopathy - Wenzl, Florian A.; Ambrosini, Samuele; Mohammed, Shafeeq A.; Kraler, Simon; Lüscher, Thomas F.; Costantino, Sarah; Paneni, Francesco (Frontiers in Cardiovascular Medicine, 2021)
Overlapping pandemics of lifestyle-related diseases pose a substantial threat to cardiovascular health. Apart from coronary artery disease, metabolic disturbances linked to obesity, insulin resistance and diabetes directly compromise myocardial structure and function through independent and shared mechanisms heavily involving inflammatory signals. Accumulating evidence indicates that metabolic dysregulation causes systemic inflammation, which in turn aggravates cardiovascular disease. Indeed, elevated systemic levels of pro-inflammatory cytokines and metabolic substrates induce an inflammatory state in different cardiac cells and lead to subcellular alterations thereby promoting maladaptive myocardial remodeling. At the cellular level, inflammation-induced oxidative stress, mitochondrial dysfunction, impaired calcium handling, and lipotoxicity contribute to cardiomyocyte hypertrophy and dysfunction, extracellular matrix accumulation and microvascular disease. In cardiometabolic patients, myocardial inflammation is maintained by innate immune cell activation mediated by pattern recognition receptors such as Toll-like receptor 4 (TLR4) and downstream activation of the NLRP3 inflammasome and NF-κB-dependent pathways. Chronic low-grade inflammation progressively alters metabolic processes in the heart, leading to a metabolic cardiomyopathy (MC) phenotype and eventually to heart failure with preserved ejection fraction (HFpEF). In accordance with preclinical data, observational studies consistently showed increased inflammatory markers and cardiometabolic features in patients with HFpEF. Future treatment approaches of MC may target inflammatory mediators as they are closely intertwined with cardiac nutrient metabolism. Here, we review current evidence on inflammatory processes involved in the development of MC and provide an overview of nutrient and cytokine-driven pro-inflammatory effects stratified by cell type.